456 Esomeprazole Use in Upper Airway Stimulation Patients Associated with Lower Functional Threshold. (3rd May 2021) - Klug, Theodore; Sagalow, Emily; Ananth, Ashwin; Huntley, Colin; Boon, Maurits
Abstract: Introduction: Proton pump inhibitors (PPIs) are widely used for gastroesophageal reflux disease (GERD) despite possible side effects including increased susceptibility to infections, secondary hypergastrinemia, and incomplete absorption of micronutrients. Upper airway stimulation (UAS) surgery involves delivering an electrical impulse to the distal hypoglossal nerve for the management of obstructive sleep apnea.. The functional threshold (FT) is the minimum stimulation required to achieve bulk tongue motion. The minimum therapeutic amplitude (MTA) is the lowest voltage required to achieve clinical benefit during titration at postoperative attended overnight polysomnography. We sought to analyze the effect of perioperative PPI use upon patients who had undergone upper airway stimulation (UAS) surgery. We hypothesized that the ion transport-related effects of PPIs would impact the amplitude necessary for tongue protrusion (FT) and clinical benefit (MTA). Methods: A retrospective chart review was conducted at a single tertiary care facility. Baseline demographic data, medication history, and comorbidities were collected from December 2014 through August 2019 on patients undergoing UAS surgery. Patients that were taking a PPI at the time of surgery and postoperatively were included. Results: 167 patients that underwent UAS surgery between 2014 – 2019 were studied. 74 patients were found to be taking a PPI perioperatively. Specifically, 38 patients were found to be on omeprazole, compared to 17 on pantoprazole, 13 on esomeprazole, 4 on lansoprazole, and 2 on rabeprazole. Overall, esomeprazole was a statistically significant predictor (p=0.0359) of a lower functional threshold amplitude: 1.58 mV in controls as compared to 2.09 mV for omeprazole, 2.12 mV for pantoprazole, 2.14 mV for lansoprazole, and 2.7 mV for rabeprazole. Use of PPI, while associated with lower FT voltage, was not a predictor of statistically significant changes in initial UAS minimum therapeutic amplitude settings. Conclusion: The functional threshold amplitude for patients taking esomeprazole was significantly different compared to patients not on a PPI. However, the use of PPI overall was not a statistically significant predictor of initial difference in UAS mean therapeutic amplitude settings. Future studies examining tolerance of therapy and voltage changes over time in patients on proton-pump inhibitors are needed. Support (if any):